Analisis Kualitas Layanan dan Strategi Promosi dalam Mempengaruhi Keputusan Anggota untuk Menabung di BMT Fajar Bina Sejahtera Cabang Metro (International Forum of Researchers and Lecturers, 2026)
This study aims to determine the effect of service quality and promotion on members' saving decisions at BMT Fajar Bina Sejahtera Metro Branch. This research uses a quantitative approach with data collection through questionnaires given to 98 respondents, selected using purposive sampling technique. Data analysis was conducted using multiple linear regression with the help of SPSS software. The results show that both service quality and promotion have a positive and significant effect on saving decisions, both partially and simultaneously. However, service quality has a more dominant influence compared to promotion. The coefficient of determination (Adjusted R²) indicates that 32.4% of the variation in saving decisions can be explained by these two independent variables. Therefore, BMT Fajar Bina Sejahtera needs to continuously improve service quality and design more effective promotional strategies to attract and retain members to be more active in saving. This research provides important insights for BMT management in formulating more precise policies to enhance members' saving decisions.